Do the Growth of Original Local Government Revenues and the Growth of Capital Expenditure Affect Fiscal Stress? - Iqbal Lhutfi; Hamzah Ritchi; Ivan Yudianto (Universitas Hayam Wuruk Perbanas, 2020)
This study aims to determine and analyze the effect of original local government revenue growth and local government capital expenditure growth on fiscal stress in regencies/municipalities in West Java Province. This study employed all 27 regencies/municipalities in West Java Province in 4 (four) periods from 2013 to 2016. This study used multiple regression analysis (panel data) and performed classical assumption tests. Because in the literature, no measurement meets the characteristics of local government budgets in Indonesia. The authors introduced a new approach by applying the fiscal capacity formula to measure fiscal stress. This study's results indicate that the growth in original local government revenue and the growth in local government capital expenditures simultaneously have a positive effect on fiscal stress in regencies/municipalities in West Java Province. The growth of local government revenue partially has a negative effect on fiscal stress in regencies and municipalities in West Java Province. The growth of capital expenditures partially has an insignificant effect on fiscal stress in regencies and municipalities in West Java Province. This research implies that the measurement of fiscal pressure is carried out using the fiscal capacity index as a new alternative that can be used by local governments to design policies.